STUDI NUMERIK KARAKTERISTIK VORTEX GENERATOR PADA MODIFIKASI AIRFOIL JOUKOWKSI DAN PADA SILINDER Re = 100,000 - Fajar Anggara; Dedik Romahadi; Subekti; Alief Avicenna Luthfie (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Utilization of ocean wave energy is one of the renewable energy sources with high potential in Indonesia. The use of Vortex Induced Vibration (VIV) has been widely developed by researchers, where the vortex will self-excite to create vibrations. Of course, its efficiency will increase when installed simultaneously to form a row. Wake Induced Vortex (WIV) has greater potential because it adds vibration through a vortex generator in a row of VIVs in the wake area. This study studied the characteristics of the vortex generator that will be used in WIV. The research method used CFD simulation Fluent 2025 with 3-dimensional geometry. The mesh used is 700 thousand in the form of a hexahedral. Independent mesh studies have been conducted so that the number of meshes 700 thousand is the most optimal and does not affect the simulation results. The Y+ value used is 1, so the mesh thickness close to the wall for Re 100,000 is 1 mm. The location of the flow separation greatly affects the vortex structure and shedding frequency of each geometry. Whereas airfoil produces bigger power but it has less frequency shedding than cylinder.